Henry James’s Spectral Archaeology - Stefano Evangelista (Transatlantica)
This article examines the depiction of archaeology in Henry James’s short story “The Last of the Valerii” (1874). Looking, at the same time, back to Prosper Merimée’s use of the fantastic in “La Venus d’Ille” (1837) and forwards to Sigmund Freud’s parallel between archaeology and psychoanalysis in “The Aetiology of Hysteria” (1896), James sets up an intricate set of relations and metaphorical correspondences between stone and language, sculpture and literature, antiquity and modernity, aesthetics and psychology. “The Last of the Valerii” participates in a literary tradition of the archaeological fantastic that developed alongside the rise of classical archaeology as a tool of Altertumswissenschaft, in which authors employ narratives of the return of material objects from antiquity in order to explore difficult questions to do with transgressive desires, repression and sexual identity.